The Steger Homestead Kitchen : Simple Recipes for an Abundant Life - Steger, Will; Steger, Rita Mae (Book collections on Project MUSE., 2022)
A down-to-earth collection of meals and memories gathered at the Homestead, the home of the Arctic explorer and environmental activist Will Steger. Will's niece, Rita Mae Steger, creates delicious and hearty meals that have become a cornerstone experience for visitors from all over the world. Now you can make these simple, hearty meals in your own kitchen-- while sharing Will's stories of Earth's most remote and endangered regions.-- adapted from inside front cover